A new genus and species of cricket from eastern Cuba: the first Antillean true Eneopterinae (Orthoptera: Gryllidae: Eneopterinae) - Yong, Sheyla; Desutter-Grandcolas, Laure; Teruel, Rolando; Leguin, Elise-Anne (Zootaxa, 2020)
The occurrence of true Eneopterinae in the Antilles is recorded herein for the first time, with the description of a new genus and species herein described from eastern Cuba (Greater Antilles): Antillobinthus inexpectatus Yong & Desutter-Grandcolas, n. gen. n. sp. It is described and illustrated in detail, including color photographs of habitus, morphologically diagnostic characters and habitat. The present finding revives a biogeographical debate, as no Eneopterinae was up-to-now known from the Antilles.